Sustainable Real Exchange Rates in the New Eu Member States : What Did the Great Recession Change? - Smidkova, Katerina (IMF Working Papers; Working Paper ;, 2010)
The Great Recession affected export and import patterns in our sample countries, and these changes, coupled with a more volatile external environment, have profound impact on our estimates of real exchange rate misalignments and projections of sustainable real exchange rates. We find that real misalignments in several countries with pegged exchange rates and excessive external liabilities widened relative to earlier estimates. While countries with balanced net trade positions are expected to continue to experience appreciation during 2010-2014, several currencies are likely to require real depreciation to maintain sustainable net external debt. Our estimates point to somewhat larger disequilibria than those of IMF country teams, however, any estimates of equilibrium exchange rates are subject to sizable uncertainty.